Protection of catalpol against triptolide-induced hepatotoxicity by inhibiting excessive autophagy via the PERK-ATF4-CHOP pathway - Zhang, Linluo; Li, Changqing; Fu, Ling; Yu, Zhichao; Xu, Gengrui; Zhou, Jie; Shen, Meiyu; Feng, Zhe; Zhu, Huaxu; Xie, Tong; Zhou, Lingling; Zhou, Xueping (PeerJ, 2022)
Catalpol significantly reduces triptolide-induced hepatotoxicity, which is closely related to autophagy. The aim of this study was to explore the unclear protective mechanism of catalpol against triptolide. The detoxification effect of catalpol on triptolide was investigated in HepaRG cell line. The detoxification effects were assessed by measuring cell viability, autophagy, and apoptosis, as well as the endoplasmic reticulum stress protein and mRNA expression levels. We found that 5–20 µg/L triptolide treatments increased the levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST), and lactate dehydrogenase (LDH), as well as the expression of autophagy proteins including LC3 and Beclin1. The expression of P62 was downregulated and the production of autophagosomes was increased, as determined by transmission electron microscope and monodansylcadaverine staining. In contrast, 40 µg/L catalpol reversed these triptolide-induced changes in the liver function index, autophagy level, and apoptotic protein expression, including Cleaved-caspase3 and Cleaved-caspase9 by inhibiting excessive autophagy. Simultaneously, catalpol reversed endoplasmic reticulum stress, including the expression of PERK, which regulates autophagy. Moreover, we used the PERK inhibitor GSK2656157 to prove that the PERK-ATF4-CHOP pathway of the unfolded protein response is an important pathway that could induce autophagy. Catalpol inhibited excessive autophagy by suppressing the PERK pathway. Altogether, catalpol protects against triptolide-induced hepatotoxicity by inhibiting excessive autophagy via the PERK-ATF4-CHOP pathway. The results of this study are beneficial to clarify the detoxification mechanism of catalpol against triptolide-induced hepatotoxicity and to promote the application of triptolide.
Keywords: Hepatotoxicity; Autophagy; ERS; Triptolide; PERK; Catalpol